Branded Content and Entertainment in Advertising A Theoretical and Empirical Study of Creative Advertising Practices - Rodríguez-Rabadán, María (Routledge, 2026)
In recent years, branded content and entertainment have become standard practice for brands, advertising agencies, and production companies. This volume analyzes branded content through a theoretical and empirical study to examine the factors that have led to exponential growth and the adaptation of creative advertising processes in the creation of branded content. The book debates the suitability and acceptability of branded entertainment as an advertising practice, the different degrees of involvement of the brand in creating content, and the brands' mastery of entertainment. It explores the implications that may underpin the practice and discusses the necessary creative elements involved in their successful execution, as well as the effects it has on consumers and audiences. This insightful book will be a valuable guide for academics and upper-level students across marketing disciplines, including advertising, brand management and communications, as well as screenwriting.
Keywords: branded content; branded entertainment; advertising; creativity